2015
DOI: 10.1002/jez.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a warm‐temperature acclimation‐associated 65‐kDa protein encoded by a temperature‐ and infection‐responsive gene in the Kumgang fat minnow Rhynchocypris kumgangensis

Abstract: Water temperature is one of the most important factors in fish physiology; thus, it is important to identify genes that respond to changes in water temperature. In this study, we identified a warm- temperature acclimation-associated 65-kDa protein (Wap65) in the Kumgang fat minnow Rhynchocypris kumgangensis, a small, cold-freshwater fish species endemic to Korea. Kumgang fat minnow Wap65-1 (kmWap65-1) was cloned using polymerase chain reaction (PCR)-based strategies, and was found to be highly homologous with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…In a previous study, we isolated Wap65‐1 from Kumgang fat minnow (kmWap65‐1) and demonstrated sensitivity of the gene to temperature changes and bacterial infection (Im et al., ). Here, we identified an isoform of kmWap65 in liver tissue of the fish, designated kmWap65‐2, and compared the expression profiles of both genes in response to physiological stress stimuli, including temperature changes, bacterial infection, and exposure to environmental toxin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we isolated Wap65‐1 from Kumgang fat minnow (kmWap65‐1) and demonstrated sensitivity of the gene to temperature changes and bacterial infection (Im et al., ). Here, we identified an isoform of kmWap65 in liver tissue of the fish, designated kmWap65‐2, and compared the expression profiles of both genes in response to physiological stress stimuli, including temperature changes, bacterial infection, and exposure to environmental toxin.…”
Section: Resultsmentioning
confidence: 99%
“…We isolated kmWap65‐2 complementary DNA (cDNA) from liver tissue of Kumgang fat minnow as described previously (Im et al., ). Briefly, total RNA was isolated and reverse‐transcribed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations